2006
DOI: 10.1159/000094446
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Capacity of Mononuclear Cells to Synthesize Cytokines against an Inflammatory Stimulus in Uremic Patients

Abstract: Background: The local production of cytokines and phagocytosis is pivotal in innate immunity. Uremic patients have a high infectious morbidity, but it remains unclear if this arises from incompetence of these local cellular functions. Methods: In 30 predialysis uremic patients and 20 controls, we studied the intracellular cytokine synthesis by mononuclear cells in response to stimulation. Moreover, phagocytic activity by leukocytes was tested. Lipopolysaccharide- or mitogen-stimulated peripheral blood cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Clinical manifestations of these alterations result both from the higher concentrations of β 2 M (e.g., DRA) as well as the altered MHC/non-classical MHC function, i.e., the phenotype of β 2 M deficiency highlighted in the β 2 M knockout mice. Observations in these animals parallel the clinical observations and laboratory associations in patients with renal dysfunction: dysregulated IFN-γ production (312, 313), tuberculosis (314–316), acute infections, and suboptimal antibody responses [all reviewed in Ref. (317)].…”
Section: β2m: Synthesis and The Way Forwardmentioning
confidence: 61%
“…Clinical manifestations of these alterations result both from the higher concentrations of β 2 M (e.g., DRA) as well as the altered MHC/non-classical MHC function, i.e., the phenotype of β 2 M deficiency highlighted in the β 2 M knockout mice. Observations in these animals parallel the clinical observations and laboratory associations in patients with renal dysfunction: dysregulated IFN-γ production (312, 313), tuberculosis (314–316), acute infections, and suboptimal antibody responses [all reviewed in Ref. (317)].…”
Section: β2m: Synthesis and The Way Forwardmentioning
confidence: 61%
“…It has been shown that PMNLs from healthy subjects react differently to uremic toxins than PMNLs from CKD patients [ 108 , 109 ]. Mononuclear cells from CKD patients have a significantly decreased cytokine production when exposed to lipopolysaccharide [ 110 ] and a diminished proliferative response to antigens in vitro [ 111 ]. One limitation of this study is that we only determined the concentration of releasing substances based on the literature and did not measure the amount of H 2 S generated during experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue of whether host innate immune system uses classical DAMP receptors to sense the elevation of all of other water-soluble and protein-bound UTs remains unknown. It is biochemically difficult for a few classical DAMP receptors, such as TLRs and NLRs, to bind with high affinity to all of those UTs and initiate inflammation efficiently, considering that reduced expression of TLR4 is found in uremic patients (58). …”
Section: Discussionmentioning
confidence: 99%